The State of Identification Systems in Africa : A Synthesis of Country Assessments - World Bank Group (World Bank, Washington, DC, 2017)
The ability to prove one's identity is a cornerstone of participation in modern life, yet over 1.5 billion people lack proof of legal identity. As a first step in assisting its client countries to close this identity gap, the World Bank Group's ID4D initiative conducts Identity Management Systems Analyses (IMSAs) to evaluate countries' identity ecosystems and facilitate collaboration with governments for future work. To date, analyses have been conducted in 17 African countries, including Botswana, Chad, Cameroon, Cote d'Ivoire, the Democratic Republic of Congo (DRC), Ethiopia, Guinea, Lenya, Liberia, Madagascar, Morocco, Namibia, Nigeria, Rwanda, Sierra Leone, Tanzania, and Zambia.